Banki spółdzielcze i spółdzielcze kasy oszczędnościowo-kredytowe w Polsce – podobieństwa oraz różnice - Orzeszko, Teresa (Bezpieczny Bank, 2024)
Savings and credit cooperatives do not constitute a homogenous set. Two of their types have been developed and operate in Poland, i.e. cooperative banks and credit unions. The author decided to identify and classify the similarities and differences between them. As a result of this research – having considered the nature of similarities and differences between cooperative banks and credit unions, as well as the type of information sources constituting the basis for a comparative analysis – three major categories of similarities and differences were distinguished: historical, regulatory and situational. Regardless of the classification into categories, both similarities and differences between cooperative banks and credit unions were divided into permanent and variable, general and specific as well as fundamental and secondary ones. The thus performed segregation allowed for distinguishing, among others, both similarities and differences: referring directly to the essence of cooperative banks and credit unions, which – owing to their fundamental importance – were subject to a detailed analysis and characteristics, and also historical and covering the effective norms for cooperative banks and credit unions functioning, which were also discussed since they determine the first ones to a significant extent.